(3GdcGaj aj GdMOjKs - (3Gdcdjfj, CHh LYaQ, Gdcdjfj, eMeO Hf jYbhH Hf ESMGb, J (B329(3g` (B941(3es
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdeMehO dfYeJg, GdeYHhO dbOQJg (B... (3cJGH GdYbGFO, CNHQfG CHh LYaQ eMeO Hf jYbhH, bGd MOKfj YOI ef CUMGHfG (B... (3bGd(B: (3deG Ndb Gddg GdYbd GSJfWbg Ke bGd dg(B: (3CbHd aGbHd Ke bGd dg COHQ aCOHQs
(3BNQgG (B:s
(3BNQgG(B: (3bGd CHh LYaQ Ydjg GdSdGe(B: ... (3Ef GdOfjG dG JPgH MJi jHYK Gddg YR hLd QLdG efG Cgd GdHjJ jYed HcJGH Gddg YR hLd, dG jQi efcQ EdG CfcQgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B7: 145s
(3GdPQjYI, L (B17: 160s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdMOjK hGdeUWdMs